A diode pumped passively mode-locked Nd:CaGdAlO4 laser. (8th March 2016) - Rao, H; Cong, Z H; Qin, Z G; Feng, C; Wang, Q P; Liu, Z J; Zhang, X Y; Zhang, S S; Liu, Y; Men, S J; Xia, J B; Di, J Q; et al.
Abstract: A diode pumped passively mode-locked Nd:CaGdAlO4 (Nd:CGA) laser was demonstrated. By using a semiconductor saturable-absorber mirror (SESAM) as the modulator, stable mode-locked pulses with a duration of 6.0 ps and a repetition rate of 88.3 MHz have been achieved at a central wavelength of 1078.6 nm. The maximum output power of 452 mW was obtained under a pump power of 10 W.